2011
DOI: 10.1128/jcm.02262-10
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Identification of Aspergillus and Mucorales Species in Tissues Collected from Patients with Fungal Rhinosinusitis

Abstract: Rapid detection and differentiation of Aspergillus and Mucorales species in fungal rhinosinusitis diagnosis are desirable, since the clinical management and prognosis associated with the two taxa are fundamentally different. We describe an assay based on a combination of broad-range PCR amplification and reverse line blot hybridization (PCR/RLB) to detect and differentiate the pathogens causing fungal rhinosinusitis, which include five Aspergillus species (A. fumigatus, A. flavus, A. niger, A. terreus, and A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Simple PCR assays are relatively easier and more straightforward than PCR-RFLP assays and differentiation of target species mainly relies on specific primers and the length of the amplified fragments. Ease of primer design, straightforward processing, and low-cost account for the wide use of this assay in the identification of a broad range of clinically relevant fungal species, including the most common pathogenic yeasts [114], cryptic Candida species [115], onychomycoses agents [116], and Aspergillus [117,118]. Multiplicity significantly affects sensitivity and specificity resulting in a higher detection limit and non-specificity in some cases [119].…”
Section: Simple Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple PCR assays are relatively easier and more straightforward than PCR-RFLP assays and differentiation of target species mainly relies on specific primers and the length of the amplified fragments. Ease of primer design, straightforward processing, and low-cost account for the wide use of this assay in the identification of a broad range of clinically relevant fungal species, including the most common pathogenic yeasts [114], cryptic Candida species [115], onychomycoses agents [116], and Aspergillus [117,118]. Multiplicity significantly affects sensitivity and specificity resulting in a higher detection limit and non-specificity in some cases [119].…”
Section: Simple Pcrmentioning
confidence: 99%
“…Multiplicity significantly affects sensitivity and specificity resulting in a higher detection limit and non-specificity in some cases [119]. Although simple PCR does not have sufficient sensitivity to detect low numbers of target organisms and, therefore, may not provide desired results when applied directly to clinical specimens, it showed good results when used on blood cultures [120,121] or combined with reverse line blot hybridization, PCR-RLB [118]. Moreover, some of these multiplex PCR assays showed a higher degree of sensitivity when compared to phenotypic assays, such as direct microscopy and culture [116,118].…”
Section: Simple Pcrmentioning
confidence: 99%
“…Clinical and physical examinations are inconclusive (Vergara et al, 2005), and there are several reports indicating a low correlation between clinical criteria and endoscopic or imaging findings (Vergara et al, 2005). Culture remains the indispensable technique for suspected fungal infection, although its sensitivity may not exceed 50% (Zhao et al, 2011). Sensitivity of 32% and specificity of 94% have been described for direct examination, with positive and negative predictive values of 81.3% and 63%, respectively (Pulido Murillo and Gaona Hernández, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Mixed infections with Aspergillus and Mucorales have been described in patients with FRS and are considered to be the most pathogenic of agents (Montone et al, 2012;Ponikau et al, 1999;Zhao et al, 2011); it is noteworthy that they were identified by molecular techniques (mainly DNA amplification by PCR), suggesting the need to use other methodologies to identify the causative agents of this mycosis to species level (Zhao et al, 2011). It is thus important to know what fungal species is involved to ensure that a proper and effective antifungal treatment can be administered.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular and nonmolecular assays have been developed (2,12,18,29,(44)(45)(46) to improve these limitations. As the lung is the main organ affected in most cases of IA, it seems logical to investigate Aspergillus in lower respiratory tract samples.…”
Section: Discussionmentioning
confidence: 99%